STUDI KEBIJAKAN PUBLIK : REVITALISASI PASAR KAJEN KABUPATEN PEKALONGAN - Saraswati Septiana; Susilo Utomo; Muhammad Adnan (Journal of Politic and Government Studies, 2014)
Based by the phsycally construction condotions of Kajen’s market is in capable toaccommodate the traders number, so that it could be required an improvement being atraditional market which is clean and secure. The problem is : Why the revitalization policiesof Kajen’s market on its implementation raises problems? What factors are underlying theemergence of problems in the policy ?This research used the evaluation theory of public policy and strenght, weakness,opportunity, and threat (SWOT) analysis technique for analyzing about the revitalizationpolicies of Kajen’s market. The object of this research are Kajen’s market, Departement ofIndustry and Trade, Cooperation and Micro Small Medium Enterprise, Law Division inSecretariat of Pekalongan Regency, Regional Legislative Assembly in Pekalongan Regencyand PT. Tika Jaya.The results show that the revitalization policies are opposed by traders because thedevelopment of Kajen’s Market was slow, the old traders are not given priority in distributionof stall, loose strategic, and determining the appropriate assistance for traders. The problemsare resolved with negotiations facilitated by District Goverment of Pekalongan.Keyword : Public policy, Revitalization policies of Kajen’s Market, Negotiate